Physical attributes and organic matter of oxisols in sugar cane production systems - Navarro Vásquez, Miriam (2019)
The knowledge of the characteristics and physical properties of the soils in function of their management, is fundamental in the development of the cultivation of sugarcane (Saccharum officinarum L.), whose purpose was to evaluate the effect of management systems on physical attributes and matter. organic (MO) of two oxisols (Rhodic Hapludox (Rh) and Anionic Acrudox (Aa)) and sugarcane production in the municipality of Jaboticabal, São Paulo state, Brazil, on the other hand the complete block design was used randomly with four treatments and five repetitions, the treatments were: soybean / milheto / soybean (SMS), soybean / crotalaria / soybean (SCS), soybean / rest / soybean (SDS) and soybean (S). The aggregate stability index (IEA), weighted average diameter (DMP), soil density (DS), total porosity (PT), macro porosity (Ma), micro porosity (Mi), penetration resistance (RP) were measured. ) and organic matter (MO). The differences in MO, IEA, RP, PT, Ma and Mi were not significant among the management systems, in strata of 0.00 to 0.10 and 0.10 to 0.20 m, in addition differences were observed in the Rh DMP from 0.00 to 0.10 m and in Aa from 0.10 to 0.20 m and in the DS the stratum from 0.10 to 0.20 m from Aa, which showed that the use of the soil alters some physical properties, but does not affect productivity, nor the total recoverable sugar, before the fourth cut of cane of sugar.